Transcranial Magnetic Stimulation in Tremor Syndromes: Pathophysiologic Insights and Therapeutic Role - Frey, Jessica; Hess, Christopher W.; Kugler, Liam; Wajid, Manahil; Wagle Shukla, Aparna (Frontiers in Neurology, 2021)
Transcranial magnetic stimulation (TMS) is a painless, noninvasive, and established brain stimulation technique to investigate human brain function. Over the last three decades, TMS has shed insight into the pathophysiology of many neurological disorders. Tremor is an involuntary, rhythmic oscillatory movement disorder commonly related to pathological oscillations propagated via the cerebello-thalamo-cortical pathway. Although tremor is the most common movement disorder and recent imaging studies have enhanced our understanding of the critical pathogenic networks, the underlying pathophysiology of different tremor syndromes is complex and still not fully understood. TMS has been used as a tool to further our understanding of tremor pathophysiology. In addition, repetitive TMS (rTMS) pulses can modulate brain functions through plasticity effects and potentially provide therapeutic benefits. While rTMS targeted to the tremor network could potentially improve tremor symptoms, evidence for only a few studies including small patient samples with limited follow-up is available. This review aims to discuss the role of TMS in advancing the pathophysiological understanding as well as emerging applications of rTMS for treating individual tremor syndromes. The review will focus on essential tremor, Parkinson’s disease tremor, dystonic tremor syndrome, orthostatic tremor, and functional tremor.